Management Strategies for Cardiac Fibromas in Early Childhood: Comparative Analysis of Surgical Outcomes and Natural History - Datsko, Oleksii M.; Rudenko, Nadiya M.; Doronin, Oleksandr V. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Cardiac fibromas (CFs) are rare primary cardiac tumors. Defining surgical indications for CF resection in early childhood represents a challenging clinical issue and varies substantially between centers. The optimal management strategy, particularly in infants and young children, requires further generalization of accumulated clinical experience. Aim. To analyze the experience of a single specialized center in managing children with CFs and to compare the outcomes of surgical treatment with the natural course of the disease. Materials and Methods. In this retrospective single-center study (2014–2023), 12 cases of CF in early childhood were analyzed: seven patients were managed conservatively, and five underwent surgical tumor resection. Results. The median age at diagnosis was 1.1 years. Asymptomatic presentation occurred in 58 % of children, arrhythmias in 33%, and signs of heart failure (HF) in 17 %. Fibromas were most commonly located in the interventricular septum (33 %), right ventricle (33 %), and left ventricle (25 %), and less frequently in the right atrium (8 %). In the observation group (median follow-up 3.6 years), an increase in absolute tumor area was noted, while the indexed area decreased (-0.94 cm²/m²/year); no deaths were recorded, and two children required antiarrhythmic therapy. In the surgical group, complications occurred in 60 % of patients (left ventricular dysfunction, ventricular septal defect, tumor recurrence, repeat surgery). Overall survival was 100 % in both groups. Conclusions. In early childhood, CFs tend to regress relatively as the child grows. In contrast, early radical surgery is frequently associated with postoperative complications. Therefore, a stratified management strategy appears optimal: urgent resection should be performed in cases of severe arrhythmia or hemodynamic obstruction, while delayed surgery is preferable for asymptomatic patients or those with medically controlled symptoms.